A simplified approach to analysing historical and recent tritium data in surface waters. Issue 4 (11th March 2014) - Michel, Robert L.; Aggarwal, Pradeep; Araguas‐Araguas, Luis; Kurttas, Tuerker; Newman, Brent D.; Vitvar, Tomas
Abstract Tritium concentrations in river and stream waters from different locations can be compared by normalizing them using the ratio of tritium concentrations in precipitation and surface water (Cp/Cs) in the study area. This study uses these ratios in a hydrological residence time context to make regional‐ and global‐scale comparisons about river basin dynamics. Prior to the advent of nuclear weapons testing, the Cp/Cs ratio was greater than or equal to 1 everywhere because of the decay of tritium in the watershed after it was deposited by precipitation. After an initial increase in the ratios during the bomb peak, the ratio dropped to less than 1 for most surface waters in the following years. This post‐bomb change in the ratio is due to the retention of the bomb‐pulse water in watersheds on timescales that are long relative to the residence time of tritium in the atmosphere. Ratios were calculated for over 6500 measurements of tritium in river and stream waters compiled by the International Atomic Energy Agency. These measurements span the post‐nuclear era (1940s to present) and include many long‐term datasets, which make it possible to examine residence times of waters in watersheds on a global basis. Plotting Cp/Cs versus time shows that ratios tended to reach a minimum in approximately one to two decades after the bomb peak for most locations. This result suggests that changes affecting quantity and quality of river flows need to be assessed on a multi‐decadal timescale. These long lag times have significant implications for assessing climate or land‐use change impacts on a large number of river systems around the world. The continuing value of tritium in studying surface water systems for both the Southern and Northern Hemisphere is also demonstrated. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.